Few-femtosecond X-ray pulse generation and pulse duration control in a seeded free-electron laser - Fan, Weijie; Qi, Zheng; Feng, Chao; Zhao, Minghua (Frontiers in Physics, 2023)
With the development of ultrafast sciences, free electron lasers (FELs) with ultrashort pulses have become a state-of-the-art tool in ultrafast phenomena studies. In an externally seeded FEL, the output pulse duration is usually determined both by the seed laser pulse duration and the FEL amplification process, which can hardly reach the timescale of a few femtoseconds. Here through a simple method of changing the relative time delay of the two seed lasers employed in a seeded FEL, we demonstrate the possibility of generating few-femtosecond soft X-ray pulses and controlling the final FEL pulse durations. Based on theoretical calculations and practical experiments, we conduct a detailed study on the capabilities and limitations of this method with the parameters of Shanghai soft X-ray FEL facility. Start-to-end simulations indicate that we can achieve ultrashort soft X-ray FEL pulses with the pulse duration down to 5.2 fs and the final pulse durations can also be controlled in terms of the relative time delays.